Moving beyond bioclimatic envelope models: integrating upland forest and peatland processes to predict ecosystem transitions under climate change in the western Canadian boreal plain. Issue 6 (17th December 2015) - Schneider, Richard R.; Devito, Kevin; Kettridge, Nicholas; Bayne, Erin
Abstract: By the end of this century, much of the climate space of western Canada's boreal forest is expected to shift northwards and be replaced by climates that are currently associated with aspen forest, parkland and grassland ecosystems. In this study, we review the various processes that will mediate ecological responses to these projected changes in climate. We conclude that ecological transitions are unlikely to involve a gradual wave‐like shift in ecotonal boundaries. Instead, we predict that ecological changes will lag substantially behind changes in climate and that individual ecosystem components will respond at different rates. In particular, if precipitation inputs are maintained as expected, then peatlands should exhibit considerable resilience to climate change and remain a dominant feature on the landscape in 2100. Because peatlands retain large amounts of water on the landscape their continued presence may in turn slow the rate of forest loss, especially the aspen component. Thus, ecological response to climate change in the western boreal region may involve a transition to a novel ecosystem that includes peatlands and aspen as dominant features – unlike anything that exists today. Moreover, this interim stage may remain in place well into the next century, potentially providing additional time for forest‐dependent species to adapt. Copyright © 2015 John Wiley & Sons, Ltd.